2016
DOI: 10.1104/pp.16.00395
|View full text |Cite
|
Sign up to set email alerts
|

Control of Floret Symmetry by RAY3, SvDIV1B, and SvRAD in the Capitulum of Senecio vulgaris

Abstract: ORCID IDs: 0000-0002-3703-7531 (H.M.P.G.); 0000-0002-9930-1377 (V.M.R.S.); 0000-0002-8470-793X (M.K.).All members of Asteraceae, the largest flowering family, have a unique compressed inflorescence known as a capitulum, which resembles a solitary flower. The capitulum often consists of bilateral (zygomorphic) ray florets and radial (actinomorphic) disc florets. In Antirrhinum majus, floral zygomorphy is established by the interplay between dorsal petal identity genes, CYCLOIDEA (CYC) and RADIALIS (RAD), and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
75
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(85 citation statements)
references
References 50 publications
10
75
0
Order By: Relevance
“…In some inflorescences, the growth of ray florets was severally inhibited and resulted in malformation (data not shown). Interestingly, no phenotypic difference was observed in DF among different lines, in accordance with the results in Senecio (Kim et al, 2008; Garcês et al, 2016). …”
Section: Resultssupporting
confidence: 88%
See 4 more Smart Citations
“…In some inflorescences, the growth of ray florets was severally inhibited and resulted in malformation (data not shown). Interestingly, no phenotypic difference was observed in DF among different lines, in accordance with the results in Senecio (Kim et al, 2008; Garcês et al, 2016). …”
Section: Resultssupporting
confidence: 88%
“…Furthermore, it is possible that the context-specific protein complex involving GhCYC2 proteins and their co-regulators may target different downstream genes (Juntheikki-Palovaara et al, 2014). Unlike in Gerbera, RAY1, RAY2 , and RAY3 in Senecio are only involved in promoting ventral identity in ray florets, whereas no change is found in DF (Kim et al, 2008; Chapman and Abbott, 2010; Garcês et al, 2016). Therefore, although a great amount of data have shown that these CYC -like genes in Asteraceae are key regulators in regulating flower development, a much more complex regulatory system seems to stay behind the complex flower head (Fambrini et al, 2014b; Juntheikki-Palovaara et al, 2014).…”
Section: Introductionmentioning
confidence: 71%
See 3 more Smart Citations